Love Thy Neighbour: Repatriating Precarious Blackfoot Sites - Chambers, Cynthia; Blood, Narcisse (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2009)
AbstractThis paper explores responsibility for the care of significant Blackfoot placesparticularly those situated in the province of present-day Alberta. Examples ofsignificant Blackfoot sites are given and the forces that have destroyed many ofthem are recounted. The story of how Blackfoot were removed from their territory toreserves is narrated and the effect of this on Blackfoot knowledge generation andtransfer is interpreted. The forces that destroyed significant sites, since theBlackfoot removal, are described and present-day stresses on the remaining sites arerelated. Pressure to extend hydrocarbon exploration and drilling into protectedwilderness areas are offered as an example. While current legislative and policyinitiatives in Alberta to mandate the inclusion of Blackfoot perspectives in effortsto preserve and protect heritage sites are laudable, this essay offers repatriationas a model for authentic Blackfoot participation in the care of the remaining sitesand the beings who inhabit them. Repatriation acknowledges that these places areanimate beings with whom humans live. In the Blackfoot view, protecting andpreserving places is not enough. Interdependent relationships, like the one betweenhumans and the places and beings that nourish them, must be nurtured throughunimpeded access, continued use, and ceremonies of renewal such as visiting andexchanging of gifts. While Blackfoot acknowledge that the non-Blackfoot newcomersare here to stay, they continue to imagine a future where all that from which theyhave been dispossessed will be repatriated so that they may meet their sacredresponsibilities to their territory and all the beings who dwell there.